2020
DOI: 10.1002/pam.22192
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from New York City's Small Schools of Choice about High School Features that Promote Graduation for Disadvantaged Students

Abstract: The present paper uses a rich dataset based on naturally‐occurring lotteries for 68 new small non‐selective high schools in New York City, which we refer to as small schools of choice (SSCs), to address two related questions: (1) What high school features are promising levers for increasing graduation rates for disadvantaged students? and (2) What high school features helped to produce SSCs’ positive impacts on graduation rates? Our findings provide suggestive evidence that school leadership quality, teacher e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Thus, the effects of policies can depend on organizational processes already there. Other types of empirical studies suggest that intentional organizational designs-e.g., smaller schools, extended school day, and the integration of community programs-can support meaningful changes in students' test scores and graduation outcomes (Bloom et al, 2020;Dobbie & Fryer, 2011). Taken together, these studies suggest how the formal parts of an organization can have important consequences for changes in behaviors, processes, and outcomes.…”
Section: Structural Theoriesmentioning
confidence: 83%
“…Thus, the effects of policies can depend on organizational processes already there. Other types of empirical studies suggest that intentional organizational designs-e.g., smaller schools, extended school day, and the integration of community programs-can support meaningful changes in students' test scores and graduation outcomes (Bloom et al, 2020;Dobbie & Fryer, 2011). Taken together, these studies suggest how the formal parts of an organization can have important consequences for changes in behaviors, processes, and outcomes.…”
Section: Structural Theoriesmentioning
confidence: 83%
“…The teachers' attitudes toward personalization, which evolves in positive student-teacher relationships, also help students struggling in specific subject areas. For instance, Midgley, Feldlaufer, and Eccles [36] discovered that, after controlling for students' initial mathematics performance and interest, students in classrooms with high levels of personalization showed more excitement for mathematics, and their willingness to engage with the material remained high when compared to students with low levels of personalization. Moreover, students who move from low-to Personalization in Education DOI: http://dx.doi.org/10.5772/intechopen.113380 high-support classrooms improve their self-efficacy and enjoyment with respect to mathematics [37].…”
Section: Math and Reading Improvement Through Personalizationmentioning
confidence: 99%
“…Although small school attendance had a positive impact on both grade progression and graduation, the impact was not statistically significant. Scholars evaluated the impact of a small high school initiative in New York City schools, and their findings suggested that high school graduation rates increased consistently for disadvantaged students under the small high school initiative (Bloom & Unterman, 2014; Bloom et al, 2010; Schwartz et al, 2013). Given the mixed findings on small high schools, meta-analysis would help come to a new understanding based on the information across studies.…”
Section: Literature Reviewmentioning
confidence: 99%